2006
DOI: 10.1016/j.ipm.2005.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Effective search results summary size and device screen size: Is there a relationship?

Abstract: In recent years, small screen devices have seen widespread increase in their acceptance and use. Combining mobility with increased technological advances many such devices can now be considered mobile information terminals. However, user interactions with small display devices remain a challenge due to the inherent input restrictions and limited display capabilities. These challenges are particularly evident for tasks, such as information seeking. For the presentation of retrieval results we consider that a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 26 publications
5
54
0
Order By: Relevance
“…Sweeney and Crestani investigated the relationship between device display size and the summary length of web search results and found that users were the most effective with shorter summaries on all devices [20]. More generally, conventional wisdom with mobile device interface design has been to reduce the amount of scrolling required [12], but this design guideline may not be as applicable today given the greater ease of scrolling associated with the current generation of touchscreen devices.…”
Section: Information Navigation On Small Displaysmentioning
confidence: 99%
“…Sweeney and Crestani investigated the relationship between device display size and the summary length of web search results and found that users were the most effective with shorter summaries on all devices [20]. More generally, conventional wisdom with mobile device interface design has been to reduce the amount of scrolling required [12], but this design guideline may not be as applicable today given the greater ease of scrolling associated with the current generation of touchscreen devices.…”
Section: Information Navigation On Small Displaysmentioning
confidence: 99%
“…People have studied how thumbnails help users to recall their memories on previously visited web pages and how summaries help users to make correct relevance decisions [Czerwinski et al 1999;Woodruff et al 2001;Kaasten et al 2002;Sweeney and Crestani 2006]. Woodruff et al [2001] compared the efficiencies of textuallyenhanced thumbnails, plain thumbnails, and textual summaries in navigating web pages to find different types of information.…”
Section: Related Workmentioning
confidence: 99%
“…Thumbnails can be used here as well as typical text summaries, which may (Buyukkokten, Kalijuvee, Garcia-Molina, Paepcke, & Winograd, 2002) or may not use information on the structure of the document being summarized (Sweeney & Crestani, 2006). Sweeney and Crestani (2006) point to an interesting distinction between effectiveness and preference.…”
Section: Surrogatesmentioning
confidence: 99%
“…Thumbnails can be used here as well as typical text summaries, which may (Buyukkokten, Kalijuvee, Garcia-Molina, Paepcke, & Winograd, 2002) or may not use information on the structure of the document being summarized (Sweeney & Crestani, 2006). Sweeney and Crestani (2006) point to an interesting distinction between effectiveness and preference. In their study of optimal summary length for handheld device presentation they find that people prefer longer summaries on larger devices but this does not make them more accurate at using summaries to predict relevance.…”
Section: Surrogatesmentioning
confidence: 99%